Leadership in the Age of Artificial Intelligence: Assessing the Effect on Employee Performance - Pandita, Shiveta (Digital Repository of Theses, 2025)
The dynamic nature of leadership necessitates continuous evolution to align with transformative technological advancements like Artificial Intelligence (AI). This study explores the relationship between leadership, AI adoption, and employee outcomes, emphasizing the pivotal role of leadership traits in AI-driven workplaces. Effective leadership now requires AI literacy, learning agility, empathy, and ethics to navigate complexities in leading organizations with Human-AI interaction. The findings show that leadership traits collectively shape the success of AI initiatives. Leaders proficient in AI literacy drive organizational success through pathways involving AI development, usage, and team-building efforts. Empathy and ethics are shown to significantly impact employee outcomes by promoting fair, transparent, and peoplecentric AI implementations. The study further reveals that while learning agility contributes to adaptability, it requires support from technical expertise to maximize performance improvements. This research highlights how leadership traits influence AI development and usage, which serve as mediators in enhancing employee performance, commitment, and satisfaction. AI literacy enables leaders to drive technological advancements, facilitating team cohesion and boosting organizational performance. Similarly, leaders’ learning agility fosters adaptability, promoting a culture receptive to AI integration. Empathy emerges as a dual-force trait, enhancing AI adoption while nurturing positive work environments. Ethical leadership reinforces trust and transparency, critical for employee engagement and the responsible use of AI. Findings offer practical implications for organizations navigating the AI era. By investing in leadership development programs emphasizing AI literacy, learning agility, empathy, and ethics, organizations can create a balanced approach to AI integration. Such investments not only address technical challenges but also enhance employee welfare, fostering commitment, performance, and satisfaction. These findings advance the understanding of leadership’s critical role in ensuring sustainable and human-centric AI transformations, enabling organizations to harness AI's potential while maintaining a focus on employee well-being and ethical practices.